(untitled) (Academicia Globe: Inderscience Research, 2023)
Every language and culture develops a linguistic system in order to enable speakers of that language to communicate effectively. Therefore, understanding people’s cultural and linguistic behavior can facilitate communication and increase understanding across-cultures. As speaking or communicating takes place in certain social and cultural environment, culture may exert great influence on people’s use of language and their views on politeness. This paper attempts to analyze the relationship of politeness and culture.